This is not the Czech Floyd. Roma and the path of postcolonial theory to Central Europe - Slačálek, Ondřej (Romano džaniben, 2023)
The text enters the discussion on the possibility of transferring postcolonial theory and other related approaches to post-socialist countries. It presents both approaches that operate on the axis of East-West relations, but at the same time approaches that place more emphasis on the racial dimension of power relations. On the basis of the texts presented, the author traces the possibilities and limits of postcolonial theory for understanding the situation of the Czech Roma.